Effect of supplementation of Purslane (Portulacaoleracea) in hypertriglyceridemic subjects - Tarkergari, S.; Waghray, Kavita; Gulla, S. (International Journal Of Community Medicine And Public Health, 2021)
Background: Portulacaoleraca (Purslane) has several health benefits. It is listed by the world health organisation as one of the most used medicinal plants and it has been given the term ’global panacea’. Many studies have demonstrated various pharmacological effects of this plant including hypoglycaemic, hypocholesterolemic, hypotriglyceridemic and antioxidant effects. Methods: A new product was developed using dried Portulacaoleraca leaves which was similar to spice powder/ chutney powder/karampodi and is used in South India as a food adjunct. The new product developed was used for supplementation studies for 90 days (3 months) among hyper triglyceridemic subjects after receiving a written informed consent. Biochemical parameters like lipid profile, i.e., total cholesterol, low density lipoprotein cholesterol, triglycerides, high density lipoprotein cholesterol, very low density lipoprotein cholesterol, kidney function test, liver function test were assessed. Baseline information, their medical history and 24 hr dietary recall was elicited from the subjects through a pretested schedule. Results: The results have shown that the triglyceride levels were significantly decreased. Total cholesterol and its fractions in the test groups showed significant decrease from pre- supplementation to during-supplementation and were stable at post-supplementation period. Conclusions: Our results indicated that the spice powder was rich in polyunsaturated fatty acids had a strong hypotriglyceridemic effect.